Herbal supplementation improves clinical outcomes among diabetes mellitus patients - Akrom Akrom; Titiek Hidayati; Arif Budi Setianto (Intelektual Pustaka Media Utama, 2023)
Hyperglycemic conditions are still common in diabetes melllitus (DM) patients with routine therapy. Rural communities in the Special Region of Yogyakarta habitually consume herbal medicines. Herbal nutritional supplements (MHM) were developed as additional therapy to increase the success of achieving therapeutic targets for DM patients. This study aimed to identify the clinical picture of DM patients who were given MHM at public health center (PHC) in the rural areas of Bantul Regency, Yogyakarta Special Region. This retrospective study was conducted on 94 DM patients with routine therapy. Patients who met the inclusion and exclusion criteria and had agreed to the informed consent were divided into two groups. Patients in the treatment group were asked to consume herbal supplement preparations (MHM) for 20 days. On day 21, each group measured clinical outcome parameters (blood pressure, blood glucose levels, triglycerides, cholesterol, high density lipoprotein (HDL), low density lipoprotein (LDL), liver enzymes, urea, and creatinine). The mean difference test between the two groups (t-test) was carried out using a 95% confidence level. The results showed that the consumption of MHM herbal nutritional supplements for 20 days reduced blood sugar levels, Hb A1C levels, and urea levels (p<0.05). There were no differences in blood pressure, pulse, cholesterol, triglyceride, HDL, LDL, serum glutamic oxaloacetic transaminase (SGOT), serum glutamic pyruvic transaminase (SGPT), and creatinine levels between the two groups (p>0.05). Administration of MHM for 20 days increased clinical outcomes in blood sugar, HbA1c, and urea levels in DM patients at PHC.